2010
DOI: 10.1371/journal.pone.0011551
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequality in the Prevalence of Autism Spectrum Disorder: Evidence from a U.S. Cross-Sectional Study

Abstract: BackgroundThis study was designed to evaluate the hypothesis that the prevalence of autism spectrum disorder (ASD) among children in the United States is positively associated with socioeconomic status (SES).MethodsA cross-sectional study was implemented with data from the Autism and Developmental Disabilities Monitoring Network, a multiple source surveillance system that incorporates data from educational and health care sources to determine the number of 8-year-old children with ASD among defined populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
243
7
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(280 citation statements)
references
References 30 publications
26
243
7
4
Order By: Relevance
“…Recent studies on the association between socioeconomic status and the risk of autism reported conflicted results (Durkin et al, 2010;King & Bearman, 2011;Rai et al, 2012). Inequality in access to service due to different SES status of parents is not unusual.…”
Section: Socioeconomic Status and Parental Concernmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies on the association between socioeconomic status and the risk of autism reported conflicted results (Durkin et al, 2010;King & Bearman, 2011;Rai et al, 2012). Inequality in access to service due to different SES status of parents is not unusual.…”
Section: Socioeconomic Status and Parental Concernmentioning
confidence: 95%
“…In twelve ADDM sites using socioeconomic status (SES), the prevalence ratio for low to medium SES was 0.7 (95%CI: 0.64, 0.76) and that for high to medium SES was 1.25 (95%CI: 1.16, 1.35), regardless of whether a child had a pre-existing ASC diagnosis or not (Durkin et al, 2010). However, in the most recent study in Sweden, children of families with low incomes and parents with manual occupations were found to have a higher risk of ASC (odds ratio=1.4, 95%CI: 1.3-1.6) (Rai et al, 2012).…”
mentioning
confidence: 99%
“…The prevalence of developmental disabilities and intellectual disability is thus higher in low-income families, although autism may be more often diagnosed in families with more highly educated parents (Leonard et al 2011;Durkin et al 2010;King & Bearman 2011). Some conditions, such as intellectual disability and Down syndrome, are found at varying rates across racial and ethnic groups in the U.S., although the mechanisms for these patterns are unknown (Griffin, Mann & McDermott 2011;Sherman et al 2010).…”
mentioning
confidence: 99%
“…Not surprisingly, states with higher populations have higher numbers of BACB certificants. After all, states with larger populations might also be expected to have greater demand for ABA service providers, considering that ASD is reported to occur in all racial, ethnic, and socioeconomic groups (Durkin et al 2010). Additionally, these states might also have a larger pool of professionals who are pursuing a career in behavior analysis.…”
Section: Aba Services In Relation To Population Datamentioning
confidence: 99%